Investigation on the effect of spark gap in dry µ-electro discharge machining of SiC-10BN nano-composite. (7th May 2012) - Paul, Goutam; Das, Mitun; Ghatak, S.; Sarkar, S.; Nagahanumaiah; Mitra, S.
SiC-10BN nano-composite is a new generation ceramic composite material which is used in the high temperature structural application. However, it is difficult to drill in sintered SiC ceramics by conventional drilling methods due to its beneficial properties such as high hardness and superior wear resistance, etc. But SiC-10 BN nano-composite having resistivity of 45.47 ohm-cm can be machined by micro-EDM. On the other hand, the normal hydrocarbon-based dielectric results in carbon deposition on tool and on the job consequently the material removal become hindered. So in the present work investigation, micro-electro discharge machining (µ-EDM) of SiC-10BN nano-composite was performed in the absence (dry conditions) of dielectric. A comparative study on the effect of different spark gap on MRR and debris shape was carried out. A mathematical model has been developed to correlate the effect of different process parameters on debris size.